Examining the Disruptive Innovation Theory by Analysing Tesla, Inc. - Daylan, Arda (My University, 2023)
The shift to electrification with electric vehicles (EV) is regarded as a phenomenon that is expected to permanently revolutionize the whole automotive industry and social habits of customers along with global economies and supply chains. Coinciding with the trend in early 2000s, at a time when the electric vehicle market was not formed yet, a startup called “Tesla Inc.” entered the market with all-electric strategy. As both developer and pioneer of the EVs, the company had gained a serious position in the industry, while being a part of the market's formation and development in remarkably two decades. Similar to the company's progress, ‘Disruptive Innovation Theory’ is well-known concept in academia that focuses on how companies create market disruption through their innovations. Although having some overlapping aspects with the theory, Tesla’s contrasting strategies, such as market entry, necessitates examination in the focus of theory. The main goal of the study was to analyze how Tesla's approach redefines the theory of disruptive innovation by comparing and contrasting the case’s strategy with theory’s framework through three different dimensions: Tesla's disruption in the automotive industry, its high-end market entry against theory’s low-end approach, and incumbent companies respond to such innovative progress. By placing Tesla as a case, the study was designed to unfold progress of both the company and its industry from framework of the theory. Thus, regarding the qualitative research design, the development of the EV phenomenon and the company was unfolded with the process study approach for observing how the status quo in the market was formed overtime. Due to inclusiveness of the focused fields, secondary data was chosen as the source and obtained from several academic and business outputs (i.e., newspapers, company/industry, and governmental outputs) that were specifically focusing on automotive industry and the case company. Outcomes revealed that Tesla's contradictory approach did not essentially redefine the disruptive innovation theory. Although the company’s both financial and industrial growth along with its achieved position contributed to the electrification phenomenon in the industry, it instead served as an alternative business-case through following a pattern that does not comply with the theory, not only in terms of its market entry, but also in many different layers (e.g., innovation, product, marketing, organizational strategies). Additionally, the approach of the incumbents also did not fully conform to the theory: despite the governmental regulations pushing them for lowering carbon emissions, evolutionary progress (instead of revolutionary) of battery technology (in terms of performance and cost), mainstream customers preference and lack of sufficient charging infrastructure in cities were considered as the main reasons for their delay. Despite being a popular case in academia with similar case-theory comparisons, this study was constructed on the company's past to present (and even future) strategies and presented its growth pattern using up-to-date data. Contrary to previous studies, the case was analyzed not only from a market entry perspective, but also from other aspects highlighted by the theory. In addition, considering the managerial implications, the study highlighted Tesla’s case as an alternative approach in terms of positioning and developing innovations in market and the pattern to follow for other companies in the industry.
Keywords: Disruptive Innovation Theory, Disruptive Innovation, Tesla,Inc., Electric Vehicles, Electrification, Automotive Industry